From Hyperglobalization to “New Globalization”: Transnational Corporations, Geopolitical Shocks, and Resilient Global Value Chains - Chatzinikolaou, Dimos; Vlados, Charis (Mercados y Negocios, 2026)
Transnational corporations (TNCs) are central to international political economy (IPE), yet their role remains contested amid geopolitical rivalry, economic shocks, and sustainability demands. This integrative review of 264 sources from Web of Science identifies five dominant perspectives in the literature: adverse globalization (critical views of TNC power), global development (TNCs as growth engines), glocal strategies (local adaptation approaches), hyperglobalization (borderless integration), and new globalization (post-2008 reconfiguration emphasizing resilience and new regionalization). These perspectives map onto established IPE theoretical frameworks, ranging from neo-Marxist dependency theory to neoliberal institutionalism, with “new globalization” emerging as the dominant paradigm. The analysis reveals a shift from polarized debates toward recognition of a more segmented, crisis-aware global economy. Persistent research gaps concern climate alignment and Global South perspectives. We derive implications for balanced policy approaches, resilient corporate strategies, and multilateral governance reform.